Acute high altitude exposure, acclimatization and re-exposure on nocturnal breathing - Furian, Michael; Bitos, Konstantinos; Hartmann, Sara E.; Muralt, Lara; Lichtblau, Mona; Bader, Patrick R.; Rawling, Jean M.; Ulrich, Silvia; Poulin, Marc J.; Bloch, Konrad E. (Frontiers in Physiology, 2022)
Background: Effects of prolonged and repeated high-altitude exposure on oxygenation and control of breathing remain uncertain. We hypothesized that prolonged and repeated high-altitude exposure will improve altitude-induced deoxygenation and breathing instability. Methods: 21 healthy lowlanders, aged 18-30y, underwent two 7-day sojourns at a high-altitude station in Chile (4–8 hrs/day at 5,050 m, nights at 2,900 m), separated by a 1-week recovery period at 520 m. Respiratory sleep studies recording mean nocturnal pulse oximetry (SpO2), oxygen desaturation index (ODI, >3% dips in SpO2), breathing patterns and subjective sleep quality by visual analog scale (SQ-VAS, 0–100% with increasing quality), were evaluated at 520 m and during nights 1 and 6 at 2,900 m in the 1st and 2nd altitude sojourn. Results: At 520 m, mean ± SD nocturnal SpO2 was 94 ± 1%, ODI 2.2 ± 1.2/h, SQ-VAS 59 ± 20%. Corresponding values at 2,900 m, 1st sojourn, night 1 were: SpO2 86 ± 2%, ODI 23.4 ± 22.8/h, SQ-VAS 39 ± 23%; 1st sojourn, night 6: SpO2 90 ± 1%, ODI 7.3 ± 4.4/h, SQ-VAS 55 ± 20% (p < 0.05, all differences within corresponding variables). Mean differences (Δ, 95%CI) in acute effects (2,900 m, night 1, vs 520 m) between 2nd vs 1st altitude sojourn were: ΔSpO2 0% (-1 to 1), ΔODI -9.2/h (-18.0 to -0.5), ΔSQ-VAS 10% (-6 to 27); differences in acclimatization (changes night 6 vs 1), between 2nd vs 1st sojourn at 2,900 m were: ΔSpO2 -1% (-2 to 0), ΔODI 11.1/h (2.5 to 19.7), ΔSQ-VAS -15% (-31 to 1). Conclusion: Acute high-altitude exposure induced nocturnal hypoxemia, cyclic deoxygenations and impaired sleep quality. Acclimatization mitigated these effects. After recovery at 520 m, repeated exposure diminished high-altitude-induced deoxygenation and breathing instability, suggesting some retention of adaptation induced by the first altitude sojourn while subjective sleep quality remained similarly impaired.